DETERMINATION OF PSE (PALE, SOFT AND EXUDATIVE) MEAT IN PORK CARCASSES - CASTRILLÓN H., Wilson E.; FERNÁNDEZ S., Jorge A.; RESTREPO B., Luís F. (Vitae, 2009)
The PSE (pale, soft and exudative) meat condition alters the color, the texture and the flavor of pork,increasing its acidity and occasioning low water retention, low nutritional level and rejection by the consumer. To determine the presence of the PSE characteristic, the pork carcasses are evaluated by pH measurements at 45 minutes (pH45) and 24 hours (pH24 after the slaughter of the pigs. The mean pH45 values indicate that 33.65% of the carcasses present the PSE condition, 47.12% are Normal and 19.23 % can be described as DFD (dark, firm and dry). The pH24 values indicate an increase in the PSE carcasses up to 68% while the normal and DFD ones decrease to 31.23 % and 0.77%, respectively. Comparing the change of the meat characteristics from 45 min to 24 hours, after the pig slaughter , it is observed that 62.44% of the normal meat and 87% of DFD one become PSE meat and 94.85% of the initial PSE one does not suffer any transformation. The pork carcasses present high incidence of the PSE characteristics at 45 minutes as well as 24 hours, indicating that there is problems before and after the slaughter of the pigs. High statistically significant difference (P ≤ 0.01) is found for the three meat conditions evaluated at pH45 and pH24.<!–[if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!– /* Font Definitions */ @font-face font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-1610611985 1107304683 0 0 159 0; @font-face font-family:Calibri; panose-1:2 15 5 2 2 2 4 3 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:-1610611985 1073750139 0 0 159 0; @font-face font-family:Verdana; panose-1:2 11 6 4 3 5 4 4 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:536871559 0 0 0 415 0; @font-face font-family:Aldine401BT; panose-1:0 0 0 0 0 0 0 0 0 0; mso-font-charset:0; mso-generic-font-family:auto; mso-font-format:other; mso-font-pitch:auto; mso-font-signature:3 0 0 0 1 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:Calibri; mso-fareast-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; mso-fareast-language:EN-US; .MsoChpDefault mso-style-type:export-only; mso-default-props:yes; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:Calibri; mso-fareast-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; mso-fareast-language:EN-US; @page Section1 size:595.3pt 841.9pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:35.4pt; mso-footer-margin:35.4pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–>